Estimation of the dietary intake and risk assessment of food carcinogens (3-MCPD and 1,3-DCP) in soy sauces by Monte Carlo simulation - Wong, Siew Fang; Lee, Bai Qin; Low, Kah Hin; Jenatabadi, Hashem Salarzadeh; Wan Mohamed Radzi, Che Wan Jasimah; Khor, Sook Mei (Elsevier, 2020)
Quantifiable levels of 3-chloropropane-1,2-diol (3-MCPD) and 1,3-dichloro-2-propanol (1,3-DCP) were found in domestically manufactured soy-based sauces. Selected commercial foods in the Malaysian market (n = 43) were analyzed for their 3-MCPD and 1,3-DCP contents using a validated gas chromatography–mass spectrometry technique. The 3-MCPD and 1,3-DCP contents of the analyzed food samples varied from not detectable levels to 0.1223 ± 0.0419 mg kg−1 and not detectable levels to 0.025 ± 0.0041 mg kg−1, respectively. High concentrations of 3-MCPD, exceeding Malaysia's maximum tolerable limit of 0.02 mg kg−1, were found in chicken seasoning cubes (mean = 0.0898 ± 0.0378 mg kg−1). Monte Carlo simulation-based health risk assessment revealed that 3-MCPD and 1,3-DCP intakes in the 50th, 95th, and 99th percentiles were lower than 4 µg kg−1 bw day−1, the limit recommended by JECFA in 2016. Hence, it was concluded that the exposure of Malaysian citizens to chloropropanols through soy sauce consumption does not present a health risk. © 2019 Elsevier Ltd